Efficacy of Brisk Walking Exercise and Asma'ul Husna Meditation on Hypertension in Women of Fertile Age - Khoirunnisak; Azizatul Hamidiyah; Lea Ingne Reffita (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Background: Hypertension is still one of the major health problems in Indonesia, especially in women of childbearing age (WUS). Management of hypertension through non-pharmacological methods such as exercise and spiritual approaches has proven to be effective and efficient. Brisk Walking Exercise (BWE) and Dzikir Asma'ul Husna (DAH) Meditation are promising interventions in holistic blood pressure control. Objective: To determine the efficacy of the combination of Brisk Walking Exercise and Dzikir Asma'ul Husna Meditation (BWE-DAH) on systolic and diastolic blood pressure in women of childbearing age with hypertension. Methods: The research design is quasi-experimental with pre-post test control group design. The sample amounted to 34 women of childbearing age who were divided into two groups, namely the intervention group (BWE-DAH) and the control group (BWE alone). The intervention was conducted for 2 weeks. Data were analyzed using Wilcoxon and Mann-Whitney tests. Results: The intervention group showed a significant reduction in systolic (mean reduction 17.4 mmHg) and diastolic (mean reduction 7.7 mmHg) blood pressure (p<0.05). The control group only showed a significant reduction in diastolic pressure (mean 3.4 mmHg). Comparison between groups showed significant differences in systolic blood pressure, but not in diastolic blood pressure. Conclusion: The combination of Brisk Walking Exercise and Dzikir Asma'ul Husna Meditation is more effective in reducing systolic blood pressure than Brisk Walking Exercise alone. These results suggest that a spiritual approach can strengthen the effectiveness of physical interventions in the management of hypertension.